Jazz Cosmopolitanism in Accra: Five Musical Years in Ghana - Weerasinghe, Dilshan (International Library of African Music, 2023)
Review of: Jazz Cosmopolitanism in Accra: Five Musical Years in Ghana. Stephen Feld, 2012. Durham, North Carolina: Duke University Press. 78 b/w illustrations, bibliography, index, 311 pages.
Keywords: West Africa; Jazz; Cosmopolitanism; Accra; Ghana; Transnational Culture; African Music